Preparation of styrene acrylic copolymer toner resin by solution polymerization / Neo Su Siang - Neo, Su Siang (2010)
This project has investigated solution polymerization to produce toner resins. There are three stages: (i) synthesis of low molecular weight styrene acrylic copolymer; (ii) synthesis of high molecular weight styrene acrylic copolymer; (iii) mixing high and low molecular weight copolymers. Gel Permeation Chromatography (GPC) was used to study molecular weight distributions, Melt Flow Index (MFI) Instrument to study the flowability of resin, Differential Scanning Calorimetry (DSC) to study the thermal properties of resin, and acid number to quantitate the amount of acidic group in the resin. A comparison of properties between the experimental samples, patent’s claims, and commercial resins had been carried out. Preparation of low molecular weight resin has carried out by using monomers, initiator and solvent. The effects of initiator concentration on the resin’s properties of low molecular weight resin had been studied. High molecular weight resin was produced by using monomers, initiator, solvent and crosslinking agent in the system. The process started with bulk polymerization followed by solution polymerization. The variation on amount of tetra(ethylene glycol)diacrylate (TD) during solution polymerization was carried out to study the effects on resin’s properties. Commercial toner resins contain a high molecular weight portion and a low molecular weight portion. The commercial resins have glass transition temperature in the range of 63~66°C, Melt Flow Index in the range of 4~10g/10 min, and acid number in the range of 8.5~10.2 mg KOH g-1. As for high molecular weight portion, Mn is in the range of 1.93×105~3.02×105 gmol-1, Mp in the range of 8.07×105~1.7×106 gmol-1, Mw in the range of 5.5×105~6.77×105 gmol-1, Mz in the range of 1.2×106~1.5×106 gmol-1, polydispersity in the range of 2.24~3.92. While for low molecular weight portion, Mn is roughly 4×103 gmol-1, Mp around 5×103 gmol-1, Mw in the range of 6×103~7×103 gmol-1, Mz in the range of 9×103~1.1×104 gmol-1, polydispersity in the range of 1.68~1.80. The ratio of low molecular weight portion to high molecular weight portion varies from 36:64 to 60:40. In this project, the low and high molecular weight portions were synthesized separately and they were mixed at various proportions to achieve the required properties as toner resins.